Fostering Employee Relations through Communication Practices: Creating a Culture of Trust, Sharing and Transparency - Monica. M; Suhas Patel; G. Ramanaiah; Channakeshava H C; Bhavya V M (Leading the Charge: A Guide to Management, Entrepreneurship and Technology in the Dynamic Business Landscape Edition 1, 2025)
Aims: The purpose of this study is to ascertain how the Dhanturi Group of Hotels Pvt Ltd’s employee relationships are affected by good communication skills. Study Design: A descriptive study was conducted among randomly selected respondents. Place and Duration of Study: The research took place within Dhanturi Group of Hotels Pvt Ltd. Methodology: The study included 125 individuals, aged between 20 and 35, 80 of whom were men and 45 of whom were women. investigated how communication behaviors affect employee relationships using a descriptive research methodology. Surveys, interviews, and focus groups were conducted with a representative sample of 125 workers from a variety of departments to gauge opinions about communication methods and levels of trust. While the goal of qualitative analysis was to find important themes in employee experiences, survey data analysis attempted to identify trends. Results: There are statistically significant positive associations between employee relationships and sharing, transparency, and trust, according to an analysis of correlations among key factors related to positive employee relationships through effective communication. The Pearson correlation coefficients for these relationships ranged from 0.117 to 0.294. An R-value of 0.860, which suggests that these communication behaviors account for 74% of the variance in employee relationships, and an Adjusted R Square value of 0.733, which indicates a good model fit, validated the strong positive relationship between the independent variables (sharing, transparency, and trust) and the dependent variable (employee relationships). Conclusion: The study emphasizes how crucial it is to promote openness, confidence, and a sharing culture in communication methods in order to improve healthy employee connections. Transparency was found to be the strongest predictor, followed by trust, and sharing, and these findings provide insightful information for organizations looking to create focused strategies to foster a collaborative and supportive work environment. These findings also suggest possible areas for future research into interaction effects and contextual factors.